An investigation of paddle wheel Cu2(μ2-O2CCH3)4 for gas molecule adsorptions. (1st February 2020) - Ding, Chang-Chun; Wu, Shao-Yi; Zhang, Li-Juan; Zhong, Si-Ying; Chen, Xiao-Hong
Abstract : Metal organic frameworks (MOFs) have been well-known and extensively researched due to the high storage /good selectivity for gas molecules. Herein, the structures and electron paramagnetic resonance (EPR) spectra for dicopper paddle wheel MOF compound (Cu2 (µ2 -O2 CCH3 )4 with various gas molecule are theoretically investigated by density functional theory (DFT) calculations. The adsorption energies and isotherms (including pure gas molecules and the mixed ones) are calculated for the gas molecules interacting with the unsaturated Cu2 (µ2 -O2 CCH3 )4 . Both quantities exhibit the roughly consistent orders (e.g. H2 S > NH3 > CO2 > CO > H2 O > N2 > NO > H2 for isotherms and H2 S > NH3 > N2 > CO2 > NO > H2 O > H2 > CO for adsorption energies), possibly suggesting that this material may act as a potential adsorbent of these gas molecules. The catalytic property of Cu2 (µ2 -O2 CCH3 )4 for oxidation of CO and NO into non-toxic molecules and splitting of H2 O into H2 and O2 in the solvent condition are uniformly discussed. Simulation of Grand Canonical Monte Carlo (GCMC) in MS 8.0 and calculations in Langmuir model reveal that Cu2 (µ2 -O2 CCH3 )4 has good selectivity for CH4 in natural gas (CH4 /CO2 /N2 ) and SO2 in fog (SO2 /NO/NO2 /H2 O/O2 ), which would exhibit potential environmentally friendly applications. GRAPHICAL ABSTRACT: